Pengaturan Tentang Standar Minimum Bagi Pelaku Spionase Dalam Hukum Internasional - Zulfah Ismail Polanunu; Popy Tuhulele; Lucia Charlota Octavina Tahamata (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Arrangements regarding espionage carried out by diplomats of sending countries who carry out the practice of collecting highly sensitive confidential information from receiving countries can be categorized as acts of espionage, therefore practices carried out by diplomats have violated the provisions stipulated in the 1961 Vienna convention on diplomatic relations and espionage is also a violation of cooperative relations based on good faith in accordance with international law customs. The aim of the research is to find out and analyze the arrangements regarding minimum standards for espionage actors in international law, as well as how to use minimum standards in international law against espionage in a country. This study uses a normative juridical research method with legal materials used, namely primary legal materials, secondary legal materials and tertiary legal materials. Collection techniques are carried out through library research and then analyzed using qualitative methods. The results of this study indicate that espionage by diplomats has violated the provisions of the 1961 Vienna Convention in article 3 concerning the functions and duties of diplomatic officials, therefore it is necessary to have a convention that regulates espionage in peacetime and oversight of diplomats so that there are no deviations from the provisions stipulated in the 1961 Vienna convention, and how international minimum standard settings protect diplomatic officials who carry out espionage actions so that they do not get treatment outside of the cases that occur.